Oxidation State‐Based Selectivity Tuning in Transition Metal Catalysis - Zou, Tian‐Yi; Zhang, Qing‐Wei (ChemCatChem, 2024)
Tuning between different selectivity is a challenging yet promising aspect in transition metal catalysis. Traditional methods for the attainment of synthetically relevant products rely on changing the solvent, ligand or additive. Despite the existing examples, outcomes of new catalytic conditions remain elusive. Recently, a novel tuning strategy based on the oxidation state of metal has drawn our attention. This method highlights the difference in reaction pathways, exhibiting great potential for high predictability. Nonetheless, researches within this field are scarcely‐reported in the present literature, and many of which show limitations in the elucidation of mechanism. To fully handle this tactic, more in‐depth investigations are demanded. A novel selectivity tuning strategy in transition metal catalysis is reviewed and presented. It enables an inversion of enantio‐ or regioselectivity through a change in the catalyst metal's oxidation state. The divergence in outcome is often based on different reaction pathways. Therefore, if the mechanisms are fully understood, this strategy is promising to be applied in a vast range of catalytic systems.